Obesity and main urologic cancers: Current systematic evidence, novel biological mechanisms, perspectives and challenges. (June 2023) - Papavasileiou, Georgios; Tsilingiris, Dimitrios; Spyrou, Nikolaos; Vallianou, Natalia G.; Karampela, Irene; Magkos, Faidon; Dalamaga, Maria
Abstract: Urologic cancers (UC) account for 13.1% of all new cancer cases and 7.9% of all cancer-related deaths. A growing body of evidence has indicated a potential causal link between obesity and UC. The aim of the present review is to appraise in a critical and integrative manner evidence from meta-analyses and mechanistic studies on the role of obesity in four prevalent UC (kidney-KC, prostate-PC, urinary bladder-UBC, and testicular cancer-TC). Special emphasis is given on Mendelian Randomization Studies (MRS) corroborating a genetic causal association between obesity and UC, as well as on the role of classical and novel adipocytokines. Furthermore, the molecular pathways that link obesity to the development and progression of these cancers are reviewed. Available evidence indicates that obesity confers increased risk for KC, UBC, and advanced PC (20–82%, 10–19%, and 6–14%, respectively), whereas for TC adult height (5-cm increase) may increase the risk by 13%. Obese females tend to be more susceptible to UBC and KC than obese males. MRS have shown that a higher genetic-predicted BMI may be causally linked to KC and UBC but not PC and TC. Biological mechanisms that are involved in the association between excess body weight and UC include the Insulin-like Growth Factor axis, altered availability of sex hormones, chronic inflammation and oxidative stress, abnormal secretion of adipocytokines, ectopic fat deposition, dysbiosis of the gastrointestinal and urinary tract microbiomes and circadian rhythm dysregulation. Anti-hyperglycemic and non-steroidal anti-inflammatory drugs, statins, and adipokine receptor agonists/antagonists show potential as adjuvant cancer therapies. Identifying obesity as a modifiable risk factor for UC may have significant public health implications, allowing clinicians to tailor individualized prevention strategies for patients with excess body weight.